EFFECT OF SILYMARIN ON SERUM CHOLESTEROL LEVELS IN RATS - Skottova, Nina; Krecman, Vladimir; Walterova, Daniela; Ulrichova, Jitka; Kosina, Pavel; Simanek, Vilim (Biomedical papers, 1998)
Previously we have shown that perorally administered silymarin, a mixture of flavonolignans extracted from the seeds ofSilybum marianum, possesses a hypocholesterolemic effect in rats fed high cholesterol diet enriched with fat1. The aim ofthis paper was to complete the data concerning peroral and parenteral administration of silymarin. The rats fed standardlaboratory diet did not respond to peroral administration of silymarin by decrease of serum cholesterol, but the mild increasein HDL cholesterol was found. Parenterally injected silymarin failed to reduce serum cholesterol both in rats fed highcholesterol diet and standard laboratory diet. The results suggest that silymarin could act either due to the fat-mediatedimproved bioavailability and/or by inhibiting of resorption of dietary cholesterol.
Keywords: Silymarin / Serum cholesterol / High cholesterol diet